THE EFFECT OF PARTICIPATION INTENSITY, LECTURER CHARACTERS, AND LEARNING ENVIRONMENT ON STUDENT ACHIEVEMENTS OF ACCOUNTING EDUCATION STUDENTS AT MEDAN STATE UNIVERSITY - Herliani, Rini; Sinaga, Sesdian Dwi; Simanjuntak, Novi Catarina; Nasir, Muhammad (Universitas Negeri Medan, 2020)
This study aims to determine the driving factors of class participation in the achievement of Accounting Education students in the 2015 and 2017 Faculty of Economics, the State University of Medan in Accounting learning. This study uses the Ex-post Facto method, with a total population of 203 people and a sample of 135 students. In this study, data collection techniques are using a questionnaire. Data analysis techniques used were descriptive statistics, the classic assumption test, and multiple regression. The results of hypotheses tests indicate that class participation, lecturer character, learning environment, and peer interaction simultaneously do not affect academic achievement. The R Square value of 0.093, which indicates that academic achievement is influenced by the variable class participation and parenting parents by 9.3%, the remaining 90.7% is influenced by other variables not examined in this study. Keywords: Class Participation; Lecturer Character; Learning Environment; Peer; Academic Achievement.